Therapy-Recalcitrant Folliculitis Decalvans Controlled Successfully with Adalimumab - Alhameedy, Meshal M (Int J Trichology, 2019)
Folliculitis decalvans (FD) is a rare idiopathic primary cicatricial alopecia which leads to permanent destruction of hair follicular stem cell. Staphylococcus aureus as well as autoimmunity has been implicated in the pathogenesis. Treatment options include topical antiseptics, topical and systemic corticosteroids, systemic antibiotics, isotretinoin, dapsone, hydroxychloroquine, and immunomodulators. We present the therapy-recalcitrant case of FD which is controlled successfully by subcutaneous injections of Adalimumab (Humira(®)) with no serious adverse events throughout the treatment.